REPRESENTASI IDEOLOGI POPULISME DALAM PEMBERITAAN TEMPO CO - Deha, Daniel (Interaksi: Jurnal Ilmu Komunikasi, 2021)
This research discusses about the representation of populist ideology in the Tempo.co’s reporting on #2019GantiPresiden social movement. It uses a critical constructivist paradigm with a qualitative-descriptive approach. The research method used is the framing analysis method with Robert N. Entman’s framing analysis model. The results show that Tempo.co uses a language that is unique and synonymous with the concept of populism through words, sentences and images. These dictums not only show Tempo.co’s ideology, but simultaneously represent a populist ideology in its reporting. Tempo.co described the mass demonstration (social movement) as a dualism of the Indonesian political democracy system. On one side, Indonesia’s political climate is not yet familiar and passionate about populism issues, but on the other side, Tempo.co actually anticipates disruption due to the radicalism of religious-fundamentalists group. Tempo.co’s ideology represents the whole face of media politics in Indonesia which regards populism as a deviant ideology.